The effectiveness of material handling towards upgrading the operations of Sime Swede Distribution Services / Sukmawati Mohd. Sanusi - Mohd. Sanusi, Sukmawati (1994)
Sime Swede Distribution Services was set up to undertake the entire warehousing divisions of Sime Darby Berhad and operates as a public warehouse in our country. As this is the second year of it operations in warehouse operation, there are a lot of changes should be done by Sime Swede Distribution Services in order to make sure that they can reduce time , cost spending on warehouse operation as well as to maximise the profit through improving their material handling system. Therefore, this research attempts to identify any problems faced by Sime Swede Distribution through its material handlings. Also to recommend some ideas which are applicable in this warehouse in order to improve their efficiency of Sime Swede Distribution Services operations.